Programming in C++ : Object Oriented Features - China Science Publishing & Media Ltd; Rai, Laxmisha (Information and Computer Engineering ;, 2019)
The book presents an up-to-date overview of C++ programming with object-oriented programming concepts, with a wide coverage of classes, objects, inheritance, constructors, and polymorphism. Selection statements, looping, arrays, strings, function sorting and searching algorithms are discussed. With abundant practical examples, the book is an essential reference for researchers, students, and professionals in programming.